2022
DOI: 10.3390/medicina58010079
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Counseling and Management: The First Study to Report NIPT Findings in a Romanian Population

Abstract: Background and Objectives: Non-invasive prenatal testing (NIPT) has been confirmed as the most accurate screening test for trisomies 21, 18, 13, sex chromosomes aneuploidies and several microdeletions. This study aimed to assess the accuracy of cell free DNA testing based on low-level whole-genome sequencing to screen for these chromosomal abnormalities and to evaluate the clinical performance of NIPT. Materials and Methods: 380 consecutive cases from a single genetic center, from Western Romania were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…A high-risk result must be confirmed. In one study, from six high-risk results, only one was confirmed with a diagnostic of microdeletion [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A high-risk result must be confirmed. In one study, from six high-risk results, only one was confirmed with a diagnostic of microdeletion [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ongoing study is the second one conducted in Romania, focusing on a case load of 1400 cases. It follows the previous survey [3], which presented the genetic counseling and management of 380 cases. The current study compares NIPT high-risk cases with confirmed positive cases.…”
Section: Discussionmentioning
confidence: 99%
“…Public databases (DECIPHER, OMIM, NCBI) were utilized for data interpretation. Statistical analysis was performed as described earlier [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An approach of combining complementary classical genetic tests has been used even earlier to resolve rare cytogenetic findings [ 30 ]. The geneticist would discuss options for a noninvasive NIFTY-pro test which enables the identification of 6 autosomal aneuploidies (chromosomes 13, 18, 21, 9, 16, and 22), sex chromosomes aneuploidies, and 84 microdeletion syndromes [ 31 ], or invasive tests of amniotic fluid or chorionic villus for culture and subsequent karyotyping, combined with FISH and microarray analysis to render reproductive counselling for future pregnancies of the parents.…”
Section: Discussionmentioning
confidence: 99%